2017
DOI: 10.3389/feduc.2017.00038
|View full text |Cite
|
Sign up to set email alerts
|

Parental Absence Accompanies Worse Academic Achievements: Evidence Based upon a Sample of Left-Behind Children in Rural China

Abstract: In China, with the rapid urbanization and large amount of labor force migrating from rural-to-urban areas, an enormous number of children living in rural China are in the absence of parental care. The objective of the study was to investigate the academic performance of left-behind children under various statuses of parental absence. We investigated 3,076 children (1,761 non-left-behind and 1,315 left-behind) regarding their academic achievement in different subjects. We found that children with different stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…LBC whose both parents are absent in family has worst physical health, higher risk of injury, behavioural problems and lower nutrition (Fu, Bo, Xue, & Yuan, 2017). The LBC who are under the care of young caregivers are found to indulge in alcoholism, smoking, internet addiction and the emotional problems (Adhikari et al, 2014;Fu et al, 2017;Yeoh & Lam, 2016).…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…LBC whose both parents are absent in family has worst physical health, higher risk of injury, behavioural problems and lower nutrition (Fu, Bo, Xue, & Yuan, 2017). The LBC who are under the care of young caregivers are found to indulge in alcoholism, smoking, internet addiction and the emotional problems (Adhikari et al, 2014;Fu et al, 2017;Yeoh & Lam, 2016).…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…They are found to be at higher risk of sedentary life, internet addiction, use of tobacco and narcotics. Especially, girls are more likely to consume an excessive sweet beverage, watch more TV and drink alcohol and self-efficacy (Adhikari et al, 2014;Fu et al, 2017;Gao et al, 2010;Yeoh & Lam, 2016). However, Acharya, Ghimire, Bhandari, Ghimire, and Jones (2019) projected towards the possibility of higher consumption of meat and eggs with increased purchasing capacity.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Their psychological development and mental health have been the focus of domestic researchers' attention. Several studies reported that these children experience psychological adjustment problems including loneliness (Hu et al, 2014), low self-esteem (Luo et al, 2012), depression and anxiety symptoms (He et al, 2012; Luo et al, 2012; Zhao et al, 2014; Wang et al, 2015), risk behaviors (Gao et al, 2010), and poor school performance and early dropout (Dreby, 2007; Wu et al, 2015; Fu et al, 2017). Studies have reported that migration type (father-only, mother-only, or both-parent migration) and care arrangements (Zhao et al, 2009; Jia and Tian, 2010; Graham and Jordan, 2011), as well as child age (Liu et al, 2009; Fan et al, 2010) and sex (Hu et al, 2014), are associated with the mental health outcomes of LC.…”
Section: Introductionmentioning
confidence: 99%
“…The active participation of children in reading is more likely to promote early childhood language and literacy development than simply reading texts, while the praise and passion of the mother encourages children to participate in language expression in parent-child reading (Leseman and De Jong, 1998;Britto and Jeanne, 2006;Duursma, 2016). One study shows that the absence of one or both parents can have varying effects on children's academic performance, compared to an absent father, an absent mother has a much more significant impact on children's academic performance (Fu et al, 2017). We therefore hypothesize that: (1) the reading comprehension ability of leftbehind children is worse than that of parented children because the left-behind children are missing one or both parents for a long period of time; (2) an absent mother has a greater impact than an absent father on children's reading comprehension ability.…”
Section: Introductionmentioning
confidence: 99%